You are on page 1of 7

# R.

(4th edition)
Solutions

Preliminaries

1.1

## 1. We have these sets :

A = {1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20}
B = {2, 5, 8, 11, 14, 17, 20, . . .}
C = {3, 5, 7, 9, 11, 13, 15, 17, 19, . . .}

## (a) A B C = {5, 11, 17}

(b) (A B)\C = {2, 8, 14, 20}
(c) (A C)\B = {3, 7, 9, 13, 15, 19}
2. (a) A\(B\A)
A

(b) A\(A\B)

(c) A (B\A)

## 3. If A and B are sets, show that A B if and only if A B = A.

Demonstration. By definition 1.1.1, if (AB) = A, A (AB) ; so, for every x A,
we have x (A B), then x B, therefore A B. Conversely, if A B, then for
every x A, x (A B), therefore A (A B) ; also, for every x (A B), x A,
therefore (A B) A ; hence, by definition 1.1.1, if A (A B) and (A B) A,
A B = A.
4. Prove the second De Morgan Law [Theorem 1.1.4(b)] : A\(B C) = (A\B) (A\C).
Demonstration. For every x A\(B C), x A but x
/ (B C), which means that
x (A\B) or x (A\C), therefore, by definition 1.1.3a, x (A\B) (A\C) ; we
conclude that A\(B C) (A\B) (A\C). Conversely, for every x (A\B) (A\C),
x (A\B) or x (A\C), therefore x
/ (B C), so x A\(B C) ; we conclude
that (A\B) (A\C) A\(B C). By definition 1.1.1., we have A\(B C) =
(A\B) (A\C).
5. Prove the distributive laws :
(a) A (B C) = (A B) (A C)
Demonstration. For every x A (B C), x A and x (B C), which means
that x B or x C, so x A B or x A C, therefore A (B C)
(A B) (A C). Conversely, for every x (A B) (A C), x A B or
x A C, so x A and x B or x C, wich means that x A (B C),
therefore (A B) (A C) A (B C). By definition 1.1.1., we have
A (B C) = (A B) (A C).
(b) A (B C) = (A B) (A C)
Demonstration. For every x A (B C), x A or x B and C, which
means that x A or B and x A or C, so x (A B) (A C), therefore
A (B C) (A B) (A C). Conversely, for every x (A B) (A C),
x (A B) and x (A C), which means that x A (B C), therefore
(A B) (A C) A (B C). By definition 1.1.1., we have A (B C) =
(A B) (A C).

6. The symmetric difference of two sets A and B is the set D of all elements that belong
to either A or B but not both. Represent D with a diagram.
A

## (a) Show that D = (A\B) (B\A)).

Demonstration. By definition 1.1.3c, for every x A and x
/ B, we have A\B ;
likewise, for every x B and x
/ A, we have B\A. Since every x D is the set
of all elements that belong to either A or B but not both, by definition 1.1.3a,
we conclude that D = (A\B) (B\A)).
(b) Show that D = (A B)\(A B).
Demonstration. By definition 1.1.3a, for every x A or x B, we have A B.
Since D is the set of all elements that belon to either A or B but not both, by
definition 1.1.3c, if x (AB) but x
/ (AB), we have D = (AB)\(AB).
7. For each n N, let An = {(n + 1)k : k N}.
(a) What is A1 A2 ?
A1 = {2k : k N}, that consists of all natural numbers divisible by 2, and
A2 = {3k : k N}, that consists of all natural numbers divisible by 3 ; then
A1 A2 = {6k : k N}, that consists of all natural numbers divisible by 6.
(b) Determine the sets

{An : n N} and

{An : n N}.

## We have A = {An : n N} = N\1. For B = {An : n N}, a` determiner

8. a` dessiner un jour
S

## 9. We have C AB, a A and b B. By definition 1.1.6, if (a, b) f and (a, b0) f ,

with f A B, it implies that b = b0. But here, by the cartesian product (definition
1.1.5), we have (1, 1) and (1, 1) in C, hence, b 6= b0 ; in other words, C doesnt pass
the vertical line test. We conclude that C is not a function.
10. Let f (x) := 1/x2 , x 6= 0, x R.
(a) Determine the direct image f (E) where E := {x R : 1 x 2}.
We have f (E) := {x R : 1/4 x 1}.
(b) Determine the inverse image f 1 (G) where G := {x R : 1 x 4}
We have f 1 (G) := {x R : 1 x 1/2} {x R : 1/2 x 1}

11. Let g(x) := x2 and f (x) := x + 2 for x R, and let h be the composite function
h := g f .
(a) Find the direct image h(E) of E := {x R : 0 x 1}.
h := g f = g(f (x)) = (x + 2)2 . We have h(E) = {x R : 4 x 9}.
(b) Find the inverse image h1 (G) of G := {x R : 0 x 4}.
We have h1 (G) := {x R : 4 x 0}.
12. Let f (x) := x2 for x R, and let E := {x R : 1 x 0} and F := {x R : 0
x 1}. Show that E F = {0} and f (E F ) = {0}, while f (E) = f (F ) = {y R :
0 y 1}. Hence f (E F ) is a proper subset of f (E) f (F ). What happens if 0 is
deleted from the sets E and F ?
Since 0 is the only common element between E and F , then E F = {0} ; and
f (E F ) = f (0) = 02 = 0, then f (E F ) = {0}. If 0 is deleted from E and F , then
E F := and f (E F ) is not defined.
13. Let f and E, F be as in Exercice 12. Find the sets E\F and f (E)\f (F ) and show that
it is not true that f (E\F ) f (E)\f (F ).
We have E\F = {x R : 1 x < 0}, f (E) = f (F ) and f (E)\f (F ) = , therefore
f (E\F ) f (E)\f (F ).
14. Show that if f : A B and E, F are subsets of A, then f (E F ) = f (E) f (F )
and f (E F ) f (E) f (F ).
Demonstration. If we suppose y f (E F ), by definition 1.1.7, it means that, for
y = f (x), there is some x (E F ), which means that some x E or x F ; this
impllies, by definition 1.1.7 again, that y f (E) of y f (F ), therefore f (E F )
f (E) f (F ). Conversely, if we suppose y (f (E) f (F )), then y f (E) or y f (F ) ;
it follows, by definition 1.1.7, that, for y = f (x), there is some x such that x E or
x F , which means that x (E F ). This implies, by definition 1.1.7 again, that
y f (E F ), then f (E) f (F ) f (E F ). By definition 1.1.1, we conclude that
f (E F ) = f (E) f (F ).
Demonstration. Now, if we suppose y f (E F ), then, by definition 1.1.7, it implies
that for y = f (x), there is some x such that x (E F ), which means that x E
and x F ; this implies, by definition 1.1.7 again, that y = f (E) and y = f (F ), then
y (f (E) f (F )), therefore f (E F ) f (E) f (F ).
15. Show that if f : A B and G, H are subsets of B, then f 1 (G H) = f 1 (G)
f 1 (H) and f 1 (G H) = f 1 (G) f 1 (H).
Demonstration. If we suppose x f 1 (G H), then, by definition 1.1.7, for x =
f 1 (x), there is some f (x) such that f (x) f (G H), which means that some f (x)

f (G) or f (x) f (H) ; this implies, by definition 1.1.7 again, that x f 1 (G) or
x f 1 (H), then x f 1 (H) f 1 (G), therefore f 1 (G H) f 1 (G) f 1 (H).
Conversely, if we suppose x f 1 (G) f 1 (H), then x f 1 (G) or x f 1 (H) ;
it follows, by definition 1.1.7, that for x = f 1 (x), there is some f (x) such that
f (x) f (G) or f (x) f (H), which means that f (x) f (G H) ; this implies, by
definition 1.1.7 again, that x f 1 (GH), therefore f 1 (G)f 1 (H) f 1 (GH).
By definition 1.1.1, we conclude that f 1 (G H) = f 1 (G) f 1 (H).
Demonstration. Now, if we suppose we have x f 1 (GH), then, by definition 1.1.7,
for x = f 1 (x), there is some f (x) such that f (x) f (G H), which means that some
f (x) f (G) and f (x) f (H) ; this implies, by definition 1.1.7 again, that x f 1 (G)
and x f 1 (H), then x f 1 (G) f 1 (H), therefore f 1 (G H) f 1 (G) f 1 (H).
Conversely, if we suppose we have x f 1 (G) f 1 (H), then, by definition 1.1.7,
for x = f 1 (x), there is some f (x) such that f (x) f (G) f (H), which means that
f (x) f (G) and x f (H) ; this implies, by definition 1.1.7 again, that x f 1 (G)
and x f 1 (H), which means that x f 1 (G H), therefore f 1 (G) f 1 (H)
f 1 (GH). By definition 1.1.1, we conclude that f 1 (GH) = f 1 (G)f 1 (H).

## 16. Show that the function f defined by f (x) := x/ x2 + 1, x R is a bijection of R onto

{y : 1 < y < 1}.
Demonstration. We have the domain of f , which is A := {x R}. By, definition
1.1.9, to determine if f is a bijection, we first assume that f is injective and verify
that, for all x1 , x2 in the domain of f , if f (x1 ) = f (x2 ), then x1 = x2 . :
f (x1 ) = f (x2 ) = q

x1

x2
=q
x21 + 1
x22 + 1

x21
x22
=
x21 + 1
x22 + 1
x21 (x22 + 1) = x22 (x21 + 1)
x21 x22 + x21 = x21 x22 + x22
x21 = x22
|x1 | = |x2 |
x1 = x2
(square root > 0 numerator signs must agree)

## of f by solving the equation for y. We have :

y=

x
+1

x2

y 2 (x2 + 1) = x2
y 2 x2 + y 2 = x2
y 2 x2 + x2 = y 2
x2 (1 y 2 ) = y 2
x=

y
1 y2

## The range of f is B := {y R : 1 < y < 1}. Thus, f is a bijection of A onto B.

17. For a, b R with a < b, find an explicit bijection of A := {x : a < x < b} onto
B := {y : 0 < y < 1}.
a` faire
18. (a) Lets take f (x) = x + a and g(x) = x + b, for a 6= b R. We have (f g)(x) =
x + a + b = (g f )(x), but f (x) 6= g(x).

## (b) Lets take f (x) = x, g(x) = x and h(x) = x2 , for

x > 2 0 R. We have
2
[f (g + h)](x) = x + x 6= (f g)(x) + (f h)(x) = x + x .
19. (a) Show that if f : A B is injective and E A, then f 1 (f (E)) = E. Give an
example to show that equality need not hold if f is not injective.
Demonstration. In general, by definition 1.1.7, if E is a subset of A, then the
direct image of E under f is the subset f (E) := {f (x) : x E} ; thus, for x E,
we have f (x) f (E), and by definition 1.1.7, the inverse image of f (E) is
f 1 (f (E)) := {x A : f (x) f (E)} ; thus, for x E, we have x f 1 (f (E))
A ; therefore, E f 1 (f (E)). However, because f is injective, for each x E,
there is, by definition 1.1.9a, an unique f (x) such that f (x) f (E) ; therefore,
for x f 1 (f (E)), we have x E, therefore f 1 (f (E)) E. By definition
1.1.1, we conclude that f 1 (f (E)) = E.
In general, it is true that E f 1 (f (E)), but many times f 1 (f (E)) 6 E. For
example, let f (x) = sin x ; for x = 0 we have 0 E, and f (0) = sin 0 = 0, then
0 f (E), but f 1 (f (E)) = {n : n Z} =
6 E.
(b) Show that if f : A B is surjective and H B, then f (f 1 (H)) = H. Give an
example to show that equality need not hold if f is not surjective.
Demonstration. By definition 1.1.7, if H is a subset of B, the inverse image of
H under f is f 1 (H) := {x A : f (x) H} ; thus, if f (x) f (f 1 (H)) for some
x f 1 (H), then f (x) H, therefore f (f 1 (H)) H. Now, suppose we have
f (x) H, then, by definition 1.1.7, we have x f 1 (H) A, but f is surjective,

## so, by definition 1.1.9b, for every x A, f (A) = B, then f (f 1 (H)) = B ; thus,

if f (x) H, we have f (x) f (f 1 (H)), therefore H f (f 1 (H)). By definition
1.1.1, we conclude that f (f 1 (H)) = H.
In general, it is true that f (f 1 (H)) H, but many times H 6 f (f 1 (H)). For
example, let f (x) = x2 ; if we suppose there is y = 1 H, we have f 1 (H) =
and f (f 1 (H)) = =
6 H.
20.